NICER and NuSTAR observations of the Be/X-ray binary pulsar 1A 0535+262 during the 2020 November giant outburst - Jaisawal, Gaurava K.; Naik, Sachindra; Gendreau, K. C.; Arzoumanian, Z.; Jana, A.; Coley, J. B.; Malacaria, C.; Vasilopoulos, G.; Fuerst, F.; Altamirano, D.; Pottschmidt, K.; Wilms, J.; et al. (2020)
Following the detection of recent X-ray activity from the Be X-ray binary pulsar 1A 0535+262 on 2020 November 6 (ATel #14157), the Neutron Star Interior Composition Explorer (NICER) has observed the system at multiple epochs.
Keywords: Binary; Neutron Star; Pulsar; Transient